“Take a Knee” Protests in Professional Sports: An Empirical Study about the Influence on Customer Loyalty to Nike in Germany - Carsten Giebe; Lana Löffler; Sandra Schneider (Business Ethics and Leadership)
The article deals with the research of opportunities and prospects to use “Take a knee” protest in professional sports for Nike marketing purposes in terms of influencing customer loyalty to that brand. The action “Take a knee” became widely known in 2016, when the coloured quarterback of the San Francisco 49ers, Colin Kaepernick, knelt in protest while singing the national anthem of the United States of America before several games to denounce police violence against blacks and coloured people. In 2017 the European community for professional sports firstly supported that action, when Hertha BSC’s Bundesliga team went down on their knees before the kick-off of a Bundesliga game to demonstrate for diversity, tolerance and responsibility. Since Hertha BSC is equipped with the sporting goods of Nike manufacturer, the article suggested and tested the hypothesis that “Take a knee” could have an impact on customer loyalty growth to the Nike brand. The systematization of the relevant literature sources and approaches to study the demand for sports goods indicates the lack of comprehensive research on the analysis regarding the impact of the atypical advertising measures on consumer behaviour. Based on the systematization of literary sources, the article identifies the controversy of marketing activities with people who engage in politics. Furthermore, the article defines the moral role of individual athletes or teams of different sports using the example of American football and football (also known as soccer). The methodological basis of the study was analytical and comparative methods, methods of analysis, synthesis, and logical generalization. The paper presents the results of an empirical analysis based on a survey of potential customers of sporting goods in Germany in early 2020 with a sample size of 135 respondents. The authors substantiate the importance of continuous and systematic work by the advertising companies aimed at attracting famous people who are politically engaged to advertising companies as a guarantee of increasing customer loyalty. The results of the study can be useful for both business and advertising companies in terms of the choice of marketing communication tools between manufacturer and customer.